Educação científica na formação de professores da educação básica no município de Palmas-TO - Suarte, Letícia Brito de Oliveira (Universidade Federal do Tocantins, 2016)
The Science Education is sought to answer the main question of this research that understand what is the space that occupies the theme in the curriculum of teacher training? The challenge to create opportunities on scientific knowledge within the reach of teachers should be faced with viable methodologies and practices, both in training courses for teachers, graduate and continuing education, as in the institutions that guide educational policies. It is understood that the undergraduate courses, responsible for teacher training, have conceptual and practical problems on the subject. However, it is known that one of the ways to reduce the fragmentation observed in the development of science education in all disciplines, it is introduced at an early age the skills necessary for the scientific issues understanding. Thus, the aim of this study was to analyze putting into effect the process of training and internalization of Science Education Curriculum in four schools from Public State Network, Second Basic Education Cycle in the city of Palmas, TO. We used qualitative research focused on teachers on Basic Education, and the case study was conducted through questionnaires, interviews, direct observations, content analysis and finished with triangulation of the information. The results indicated the teachers' difficulty in understanding and appropriating the science education in their teaching practices, but also showed the little value attributed to it in teacher training courses. Furthermore, official documents clearly expressed the need for research in basic education, such as PCNs and DCNs, they are not able to provide the instruments necessary for the teacher to take ownership of this work methodology. Therefore, it is clear the current inability of the education system in schools practices, actions that guide for Science Education